Block of Proliferation 1 Promotes Proliferation, Invasion and Epithelial Mesenchymal Transformation in Gastric Cancer. (16th February 2022) - He, Jing; Chen, Ziwei; Xue, Qingfeng; Shi, Wenyu
Abstract : Background . Gastric cancer (GC) is one of the leading causes of cancer-related death worldwide nowadays. Block of proliferation 1 (BOP1), a nucleolar protein involved in rRNA processing and ribosome assembly, is associated with tumor development in certain cancers of digestive system. Therefore, we hypothesized that BOP1 might play an important role in gastric cancer development. Methods . Gene Expression Omnibus (GEO) database and The Cancer Genome Atlas (TCGA) were used to identify the differentially expressed genes and their clinical relevance. qPCR and western blot were performed further to examine the levels of BOP1 mRNA and protein, respectively. Cell viability, apoptosis, migration and invasion were investigated in gastric cancer cell lines with BOP1 silencing or overexpression. The epithelial mesenchymal transition (EMT) associated proteins, including E-cadherin and N-cadherin, were measured using immunoblotting. Finally, the downstream pathway of BOP1 were explored using bioinformatic analysis and qPCR. Results . BOP1 was found up-regulated in gastric tumor tissues compared with paired normal tissues (P < 0.0001). Its expression was associated with more advanced pathological grades (P = 0.0006) and tumor location (P = 0.002), as well as a poor survival (HR 1.27, P = 0.015). BOP1 expression was increased in 4 kind of tumor cell lines compared with the normal group. The overexpression of BOP1 promoted cell proliferation and inhibit cell apoptosis, while silencing BOP1 showed a reversed trend. Immunoblotting results suggested that BOP enhanced N-cadherin, a mesenchymal marker, while reduced E-cadherin, an epithelial marker. Finally, bioinformatic prediction showed that the cell cycle could be a downstream pathway of BOP1. Conclusions . The present study demonstrated that BOP1 contributed to the development of gastric cancer by promoting proliferation, invasion and epithelial mesenchymal transformation, which could be a biomarker or therapeutic target in GC.